ALTERED LIPID PROFILE ASSOCIATED WITH POLYCYSTIC OVARIAN SYNDROME WOMEN OF TAMILNADU - R. JAYASREE; M. VIJAYALAKSHMI (The Bioscan, 2010)
The lipid profile of PCOS women were investigated between the age group of 25 – 37 years who were age, sex matched with 46 control healthy individuals. 10mL of blood was collected from each subject by venipuncture and the lipid profile was estimated. There was a significant (p<0.01) rise in triglyceride, cholesterol, LDL and a significant fall in HDL (p<0.01) levels of PCOS women as compared to the controls. The dyslipidaemia associated in PCOS women may contribute to the risk of cardiovascular diseases reported at later stages in them.